Digital Literacy: Education for Safe Internet Usage - Nuning Kurniasih (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
Digital literacy has an important role in preventing cybercrime. This Community Service Program (PKM) aims to increase public awareness of using the internet safely, positively and creatively. This PKM activities is a form of my participation as one of the speakers in the series of events